Weshare wp individual part: literature review and in-depth analysis United Kingdom - Erbach, Henri (2022)
This work project individual part first reviewed the literature on export vs. FDI market entry modes, followed by an in-depth market analysis of the United Kingdom. The purpose of this in-depth analysis is to add further detailed information to the previous country ranking and cluster analysis. The following areas were examined in the in-depth analysis: contacts, competition, market sales and company sales potential and the market entry conditions. The findings show that the UK is a market with a lot of potential, but it also has some challenging market entry conditions for car-sharing companies.